2019
DOI: 10.1590/1678-992x-2018-0002
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological characterization of Coffea arabica cultivar IPR 106 resistance to Meloidogyne paranaensis

Abstract: Meloidogyne species are widely distributed in coffee growing areas in Brazil, where M. paranaensis is responsible to significant losses to the crop. One of the main management strategies is the use of resistant cultivars, such as Apoatã rootstock and cultivars IPR 100 and IPR 106. However, the parasitic relationship between coffee and M. paranaensis in cultivars carrying resistance genes has been poorly understood. The objective of this paper was to characterize the resistance response of Coffea arabica cv. IP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…The resistance to both nematodes observed in this study confirmed previous findings of the simultaneous resistance of this cultivar against the nematodes M. incognita and M. paranaensis (Ito et al 2008). Another histopathological study reported that the resistance of IPR 106 is apparently due to hypersensitive-like response and was detected at 30 days after inoculation with population 98.1 of M. paranaensis, when abnormal giant host cells were observed and malformed nematode females (Shigueoka et al 2019). IPR 106 has not yet been tested for all known M. exigua and M. incognita races.…”
Section: Nematode Resistancementioning
confidence: 99%
“…The resistance to both nematodes observed in this study confirmed previous findings of the simultaneous resistance of this cultivar against the nematodes M. incognita and M. paranaensis (Ito et al 2008). Another histopathological study reported that the resistance of IPR 106 is apparently due to hypersensitive-like response and was detected at 30 days after inoculation with population 98.1 of M. paranaensis, when abnormal giant host cells were observed and malformed nematode females (Shigueoka et al 2019). IPR 106 has not yet been tested for all known M. exigua and M. incognita races.…”
Section: Nematode Resistancementioning
confidence: 99%